Protein Intake, Especially Vegetable Protein Intake, Is Associated with Higher Skeletal Muscle Mass in Elderly Patients with Type 2 Diabetes - Akane Miki; Yoshitaka Hashimoto; Shinobu Matsumoto; Emi Ushigome; Takuya Fukuda; Takafumi Sennmaru; Muhei Tanaka; Masahiro Yamazaki; Michiaki Fukui (Journal of Diabetes Research)
Background/Aims. Protein intake is important for maintaining muscle mass in general population. However, it remains to be elucidated the association between dietary protein intake and skeletal muscle mass in elderly patients with type 2 diabetes. Methods. In this cross-sectional study of 168 elderly patients with type 2 diabetes, we investigated the relationship between skeletal muscle index (SMI) and protein intake. Bioimpedance analysis was used for measurement for skeletal muscle mass (kg) and SMI (%), which was defined as skeletal muscle mass (kg)/total body weight (kg) × 100. Habitual food and nutrient intake were estimated by a questionnaire. Results. Protein intake was independently correlated with SMI after adjusting for age, hemoglobin A1c, C-peptide index, exercise, smoking, insulin treatment, total energy intake, and C-reactive protein (standardized regression coefficient = 0.664, P<0.001 in men and standardized regression coefficient = 0.516, P=0.005 in women). Additionally, the animal protein to vegetable protein ratio was negatively correlated with SMI after adjusting for covariates in men (standardized regression coefficient = −0.339, P=0.005). Conclusions. We found that total protein intake, especially vegetable protein intake, was positively associated with skeletal muscle mass in elderly patients with type 2 diabetes.